(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Factoring has been a popular method of financing of companies in India. Since its inception, factoring business has made a significant progress in India. The total factoring volume has increased in the past nine years. Yet it is found that in its present improved format, factoring is still not the preferred solution for most of the Indian Companies. But around the world, factoring is a popular option to access working capital in the case of small or even large businesses, among eleven companies, which are providing the factoring business in India, only State Bank of India Global Factors Limited (SBIGFL) is providing domestic as well as International Factoring services under one roof. S BIGFL is a member of Factors Chain International (FCI), an Umbrella Organization of worldwide factoring companies. The aim of this study is to know the concept of factoring and the products, services, role of the SBIGFL in the factoring business in India.